RNHSO2F as Reliable Azasulfene Precursors for the Construction of Sulfamates - Guo, Taijie; Wang, Wei; Xu, Long; Dong, Jiajia (Synthesis, 2025)
The utilization of NH-sulfamoyl fluorides (RNHSO2F) as reliable SuFEx synthons for the construction of various sulfamate esters is reported. By using potassium fluoride as base, we were able to convert RNHSO2F into azasulfene intermediates under mild conditions and guarantee their further efficient ligation with phenols and alcohols.
Keywords: SuFEx; NH-sulfamoyl fluorides; sulfamate esters; azasulfene intermediates; potassium fluoride